Unveiling Growth: Do Master's Degrees Propel Professional Development for English Teachers at All Experience Levels? - Tanjung, Muhammad Rafiq; Kurniawan, Eri (VELES Voices of English Language Education Society, 2024)
Teachers, as professional educators, are supposed to keep improving their ability in the pedagogical field. The teacher development program is one of the best ways for teachers to maintain and enhance their professionalism. Motivation has become an issue that is considered crucial to teachers' involvement in teacher development programs (TPD). However, investigating novice and experienced EFL teachers' motivation in pursuing their master's degree as a form of development activity is underexplored. This research article aims to investigate novice and experienced English teachers' voices regarding their motivation in pursuing a master's degree at a postgraduate program in one of the state universities in Bandung and the comparison between the teachers in regard to their motivation. This study employed a qualitative research approach guided by a case study design with 2 novice English teachers and 3 experienced English teachers who are currently studying at a postgraduate program as the respondents. The instrument used in this study was an interview with 9 questions adapted from a conceptual framework proposed by Alghamdi (2020). The findings revealed that the EFL teachers have several types of factors in their motivation to pursue their higher education. The factors are primarily grouped into incentive and reward factors, school factors, CPD program factors, and within-teacher factors. In comparison, all respondents have quite similar motivations with no significant difference. However, one difference was found in the reward factor in which the role of the family is more motivating in novice teachers than inexperienced teachers.